The Future of Logistics: SAP EWM and Autonomous Vehicles in Smart Warehouse Automation - Chakraborty, Alok (Transactions on Engineering and Computing Sciences, 2025)
The rapid advancement of autonomous vehicles (AVs) has led to their increasing adoption in logistics and warehouse operations. When integrated with SAP Extended Warehouse Management (EWM), autonomous vehicles can significantly enhance the efficiency, flexibility, and automation of warehousing processes. This study investigates the integration of SAP EWM with autonomous vehicles, such as automated guided vehicles (AGVs), autonomous forklifts, and drones, to establish smart warehouses capable of managing and optimizing inventory, material handling, and order fulfillment with minimal human intervention. This research examines the technical aspects of integration, potential benefits and challenges, and the impact of autonomous vehicles on warehouse productivity, safety, and operational costs.